Beban Kerja, Burn Out, Jenjang Karir, Employee Engagement terhadap Loyalitas Karyawan Pada Kantor Kelurahan Harapan Jaya Bekasi Utara - Nawang Dwi Anjani; Dewi Puspaningtyas Faeni; Novita Wahyu Setyawati (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This study aims to determine workload, burn out, career path, employee engagement on employee loyalty at the Harapan jaya village office, North Bekasi. Using a descriptive quantitative approach method by distributing a 1-5 Likert scale. The employee population is 65 employees and the sample used was 65 samples. Research using Smart PLS 3.0 software. The results of this study the workload variable has a P-Values value of 0.731 or <0.05, so it can be stated that workload has a significant negative effect on employee loyalty. The burn out variable has a P-Values value of 0.759 or <0.05, workload has a significant negative effect on employee loyalty. The career path variable has a P-Values value of 0.012 or <0.05, workload has a significant positive effect on employee loyalty. The employee engagement variable has a P-Values value of 0.022 or <0.05, workload has a significant positive effect on employee loyalty. While the results of simultaneous research from workload variables, burn out, career path, employee engagement are positive and significant to employee loyalty with an F-count value of 26. 425> F-table 1.40 and the coefficient of determination (R2) on R-Square obtained a value of 56.7%. Keywords: Workload, Burn Out, Career Path, Employee Engagement, Employee Loyalty